TRPC1 Channels Are Expressed in Pyramidal Neurons and in a Subset of Somatostatin Interneurons in the Rat Neocortex - Martinez-Galan, Juan R.; Verdejo, Ana; Caminos, Elena (Frontiers in Neuroanatomy, 2018)
Disturbances in calcium homeostasis due to canonical transient receptor potential (TRPC) and/or store-operated calcium (SOC) channels can play a key role in a large number of brain disorders. TRPC channels are plasma membrane cation channels included in the transient receptor potential (TRP) superfamily. The most widely distributed member of the TRPC subfamily in the brain is TRPC1, which is frequently linked to group I metabotropic glutamate receptors (mGluRs) and to the components of SOC channels. Proposing TRPC/SOC channels as a therapeutic target in neurological diseases previously requires a detailed knowledge of the distribution of such molecules in the brain. The aim of our study was to analyze the neuroanatomical distribution of TRPC1 in the rat neocortex. By double- and triple-labeling and confocal microscopy, we tested the presence of TRPC1 by using a series of specific neurochemical markers. TRPC1 was abundant in SMI 32-positive pyramidal neurons, and in some GAD67 interneurons, but was lacking in GFAP-positive glial cells. In neurons it colocalized with postsynaptic marker MAP2 in cell bodies and apical dendritic trunks and it was virtually absent in synaptophysin-immunoreactive terminals. By using a panel of antibodies to classify interneurons, we identified the GABAergic interneurons that contained TRPC1. TRPC1 was lacking in basket and chandelier parvalbumin (PVALB) cells, and a very low percentage of calretinin (CALR) or calbindin (CALB) interneurons expressed TRPC1. Moreover, 63% of somatostatin (SST) expressing-cells and 37% of reelin-positive cells expressed TRPC1. All the SST/TRPC1 double-labeled cells, many of which were presumptive Martinotti cells (MC), were positive for reelin. The presence of TRPC1 in the somata and apical dendritic trunks of neocortical pyramidal cells suggests a role for this channel in sensory processing and synaptic plasticity. Conversely in SST/reelin interneurons, TRPC1 could modulate GABAergic transmission, which is responsible for shaping the coordinated activity of the pyramidal cells in the cortical network. In future studies, it would be relevant to investigate whether TRPC1 could be involved in the expression or processing of reelin in SST inhibitory interneurons.